(untitled) (International Research in Economics and Finance, 2018)
This paper applies the annual data series from 1983 to 2016 and introduces an employment variable to analyze the interaction among foreign direct investment, economic growth and employment. Three variables are used to conduct an empirical analysis under the VAR model. Via the analysis of Augmented Dickey-Fuller test, Granger causality test, impulse response function and variance decomposition, the results show that the foreign direct investment has a positive effect on economic growth and employment, and the economic growth has a positive effect on employment. The employment and economic growth exist bidirectional causality. Meanwhile, the foreign direct investment can also result in an increase in the employment. More importantly, this paper provides some ideas for China’s government to settle some social problems such as employment and economic growth. Specifically, at present, China’s government still should encourage foreign investors to invest in China because it can be beneficial to employment and economic growth in China. Of course, the structure of employment also should be optimized so as to keep high speed economic growth. Simultaneously, the high speed economic growth can improve the employment in China.